Identification of functional missense single-nucleotide polymorphisms in TNFAIP3 in a predominantly Hispanic population. Issue 6 (December 2018) - Zhang, Bing; Nakamura, Brooke Naomi; Perlman, Aryeh; Alipour, Omeed; Abbasi, Sadeea Qureshi; Sohn, Peter; Gulati, Alakh; Moore, Graham; Hwang, Caroline; Sheibani, Sarah; Zarchy, Thomas; Shao, Ling
Abstract: Background: Tumor necrosis factor alpha-induced protein 3 ( TNFAIP3 ) is a multifunctional ubiquitin binding and editing enzyme that regulates inflammation. Genetic studies have implicated polymorphisms within the TNFAIP3 locus to the development of numerous immune-related diseases. This study evaluated the frequencies of single-nucleotide polymorphism (SNPs) within the exonic regions of the TNFAIP3 gene and an associated point mutation from the Illumina array among a predominantly Hispanic cohort. Methods: Genomic DNA was obtained from 721 participants and sequencing of all TNFAIP3 exons and an intergenic point mutation (rs6920220) was performed. In-vitro functional assessment was performed by transfecting mutated TNFAIP3 constructs into TNFAIP3 knockout cells containing the NF-kB luciferase reporter and stimulating with TNFα. Comparative statistics were performed with Student's t -test for continuous variables and chi-squared test for categorical variables. Results: Sequencing revealed two missense SNPs, rs146534657:A>G and rs2230926:T>G, both within exon 3 of TNFAIP3, which encodes the protein's deubiquitinating enzymatic domain. Frequencies of all three point mutations differed significantly across racial groups ( χ 2 -test, P = 0.014 to P < 0.001). Compared to Caucasians, rs146534657:A>G was overrepresented among Hispanics (odds ratio (OR) [95% CI] 4.05 [1.24−13.18]), and rs2230926:T>G was more prevalent among African-Americans (OR [95% CI] 3.65 [1.58−8.43]). In-vitro assays confirm rs146534657:A>G and rs2230926:T>G decrease the ability of TNFAIP3 to abrogate NF-κB activation by 2-fold ( P < 0.01) and 1.7-fold ( P < 0.01), respectively. Conclusions: This study reports the frequency of rs146534657:A>G among Hispanics and is the first to evaluate its potential physiologic impact, establishing a basis for future research as a potential biomarker among this population.